2015
DOI: 10.5858/arpa.2014-0312-ep
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Workplace Satisfaction and Engagement of Academic Pathologists: Opportunities to Enhance Faculty Diversity

Abstract: Context.-There is attrition of women across professorial ranks in academic pathology. Women are underrepresented as leaders; 15.4% of academic pathology departments are chaired by women, according to the Association of American Medical Colleges (AAMC).Objective.-To identify areas for targeted interventions that can advance academic and leadership development of women faculty by examining (1) sex differences in career satisfaction in US medical school pathology departments participating in the AAMC's Faculty Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…6 Although these authors did not find that race or gender influenced career satisfaction, several surveys have found that women physicians, especially in selected specialties, have lower career satisfaction than men. [7][8][9] Gender differences in career satisfaction begin early and continue during career development. A survey of 1,708 early clinician researchers, who received National Institutes of Health K08 and K23 awards for mentored career development, found that although career dissatisfaction was generally low, dissatisfaction with work-life integration was high, and was significantly higher in women than men.…”
Section: Résumémentioning
confidence: 99%
“…6 Although these authors did not find that race or gender influenced career satisfaction, several surveys have found that women physicians, especially in selected specialties, have lower career satisfaction than men. [7][8][9] Gender differences in career satisfaction begin early and continue during career development. A survey of 1,708 early clinician researchers, who received National Institutes of Health K08 and K23 awards for mentored career development, found that although career dissatisfaction was generally low, dissatisfaction with work-life integration was high, and was significantly higher in women than men.…”
Section: Résumémentioning
confidence: 99%
“…There are recruitment challenges in academic medical careers due to stagnant or decreases in research funding pay lines, the need to do more clinical work to generate income, and pressure to provide teaching that is often unfunded. A recent publication by Howell et al noted the strategic importance of recruiting and retaining the growing pool of female talent in pathology 3 since 54.0% of pathology residents are women. 1 Cultivating women’s careers in academia, however, means addressing additional challenges related to work and family.…”
Section: Introductionmentioning
confidence: 99%
“…Gender issues are likely to come up, especially related to promotion and advancement 13 and to career–family–life balance. 14 For women and minorities, having at least 1 mentor who has first-hand knowledge of roadblocks and pitfalls due to gender or minority status is useful. There is literature available in these areas, however the most effective approach for the mentor is to listen carefully to the mentee since each will have their own personalized experiences and needs.…”
Section: The Mentor–mentee Relationshipmentioning
confidence: 99%
“…There is literature available in these areas, however the most effective approach for the mentor is to listen carefully to the mentee since each will have their own personalized experiences and needs. 14 Confidentiality when discussing these areas needs to be assured and followed. The mentee is pleased to have someone listen to their concerns and to offer mentorship on how to navigate what may often be difficult situations.…”
Section: The Mentor–mentee Relationshipmentioning
confidence: 99%